WEBSITE PROFIL BERBASIS CLOUD COMPUTING DENGAN MODEL LAYANAN SOFTWARE AS A SERVICES - Marhayu, Marhayu; Purwanti, Ruth Estheriana (Universitas Palangka Raya, 2014)
Website with Cloud Computing is a service that can allow users or companies to performelectronic access to information . Cloud Computing is currently very favorable in terms ofpromotion / introduce information especially in education . With the application of thesetechnologies will be constructed a